Characterization of the complete mitochondrial genome of the hybrid of wild yak (♂) × domestic yak (♀). Issue 1 (2nd January 2019) - Wu, Xiaoyun; Zhou, Xuelan; Ding, Xuezhi; Liang, Chunnian; Guo, Xian; Chu, Min; Wang, Hongbo; Pei, Jie; Bao, Pengjia; Yan, Ping
Abstract: In the present study, we reported the complete mitochondrial DNA sequence of the hybrid from wild yak (♂) × domestic yak (♀). The mitochondrial genome is 16, 322 bp in length, including the typical structure of 22 transfer RNA genes, 13 protein-coding genes, 2 ribosomal RNA genes, and 1 non-coding control region. The overall nucleotide composition is: 33.74% A, 13.18% G, 25.86% C, and 27.21% T. The phylogenetic analysis by neighbor-joining (NJ) method showed that the hybrid of wild yak (♂) × domestic yak (♀) has a closer relationship to the Qinghai Plateau yak.